2019
DOI: 10.1093/rpd/ncz105
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Tritium Around a Fusion Test Facility

Abstract: Deuterium plasma operations using a large fusion test device have been carried out since 2017 at the National Institute for Fusion Science. A small amount of tritium was produced by the fusion reaction, d(d, p)t. Then, a part of the tritium was released into the environment. Thus, monitoring the level of tritium in the environment around the fusion test facility is important. This is done before starting the deuterium plasma experiment. The environmental tritium concentrations indicated that they are at backgr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…This also suggested that there were no impacts by tritium and deuterium on the surrounding environment of the fusion test facility after the deuterium plasma experiment. Additionally, these results supported those reported by Tanaka et al [20]. A committed effective dose equivalent of 6.2 × 10 −6 mSv y −1 was estimated for an annual consumption of drinking water having the highest tritium concentration in precipitation after starting the deuterium plasma experiment (0.47 Bq L −1 ) by using a dose conversion factor of 1.8 × 10 −11 Sv/Bq [39] and a daily water intake rate of 2.0 L [40].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This also suggested that there were no impacts by tritium and deuterium on the surrounding environment of the fusion test facility after the deuterium plasma experiment. Additionally, these results supported those reported by Tanaka et al [20]. A committed effective dose equivalent of 6.2 × 10 −6 mSv y −1 was estimated for an annual consumption of drinking water having the highest tritium concentration in precipitation after starting the deuterium plasma experiment (0.47 Bq L −1 ) by using a dose conversion factor of 1.8 × 10 −11 Sv/Bq [39] and a daily water intake rate of 2.0 L [40].…”
Section: Resultssupporting
confidence: 93%
“…The tritium concentrations in environmental samples (environmental water, air, vegetation, etc.) were monitored before and after the deuterium plasma experiment to assess the impact of released tritium [17,18,19,20,21]. The tritium concentration levels were within the background range of the environmental variation.…”
Section: Introductionmentioning
confidence: 99%